Estimation of solar energy potential over Mongolia based on satellite data - Bayasgalan, Onon; Adiyabat, Amarbayar; Hashimoto, Jun; Otani, Kenji (Scientific transaction of the National University of Mongolia. Physics, 2022)
Abstract —We aim to estimate solar resource of Mongolia using satellite data in combination with limited ground measurements. Visible channel images provided by Japanese Geostationary Meteorological Satellite (GMS) Himawari 8 are correlated with ground-based measurements of solar irradiation to derive parameters of the semi-physical model.